Production of Greenhouse-Grown Peppers in Florida - Elio Jovicich; Daniel J. Cantliffe; Steve A. Sargent; Lance S. Osborne (EDIS, 2004)
In Florida, high market prices, consumer demand, and a suitable environment for growing colored peppers under protected agriculture have encouraged greenhouse growers to consider the economic viability of this crop. This document is HS979, one of a series of the Department of Horticultural Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: July 2004.